2020
DOI: 10.1039/c9ra07409k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and optimization of activated nano-carbon production using physical activation by water steam from agricultural wastes

Abstract: Production of activated nano-carbon from agricultural wastes was studied in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…This by-product is normally incinerated or dumped without control, which results in the production of large amounts of waste and pollution [2]. Several researchers have focused on different alternatives for using almond shell wastes based on their potential uses as biomass to produce renewable energy [3]; as a source of organic biopesticides [4], heavy metal adsorbents [5], dye adsorbents [6], growing media [7], the preparation of activated carbons [8] and xylo-oligosaccharides [9], antioxidants [10] or as additives in eco-friendly composites [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This by-product is normally incinerated or dumped without control, which results in the production of large amounts of waste and pollution [2]. Several researchers have focused on different alternatives for using almond shell wastes based on their potential uses as biomass to produce renewable energy [3]; as a source of organic biopesticides [4], heavy metal adsorbents [5], dye adsorbents [6], growing media [7], the preparation of activated carbons [8] and xylo-oligosaccharides [9], antioxidants [10] or as additives in eco-friendly composites [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The production process and operational parameters were proposed based on recent bibliographical data, which reported the obtaining of activated carbons from nutshells, using an inert nitrogen-based atmosphere for the pyrolysis stage and a flow of steam as an activating agent for the activation stage [13]. The parameters and conditions reported by Nazem et al [13] were considered for the conceptual plant design considering a specific area of 1248 m 2 /g for the activated carbon. This report indicates the pyrolysis stage temperature of 600 • C and a residence time of 1 h. For the activation stage, the operational conditions considered were 950 • C for temperature and 1 h for residence time.…”
Section: Production Processmentioning
confidence: 99%
“…There are various organic materials that serve as raw materials for obtaining activated coals, such as coconut shells [7], rice shells [8], palm shells [9], peanut shells [10], and nutshells [11], among others [5,6]. Recent studies have shown that physically activating carbon with steam using nutshells as a precursor has presented interesting characteristics for applications in the removal of heavy metals from effluents of polluted waters [12,13]. In this sense, it could be interesting to develop a complete economic evaluation of a nutshell activated carbon production plant, using the parameters and conditions used in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The boiling of a single bubble in a fluid of water under normal and low gravity was examined and it was concluded that the lifetime of the bubble could be adjusted based on the water temperature 15 . As can be seen, many research works have been done experimentally 16 19 and it has seen a number of limitations and difficulties. Therefore, it will be highly valuable to investigate these systems using modeling and simulation methods 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%